Body Composition Using Air Displacement Plethysmography in Children With Inflammatory Bowel Disease. Issue 1 (July 2020) - Dhaliwal, Jasbir; Martincevic, Inez; Williams, Brock; Frost, Karen; Uusoue, Krista; Arpino, Valerie; Church, Peter; Walters, Thomas D.; Griffiths, Anne M.; Mouzaki, Marialena
ABSTRACT: Objective: The aim of the study was to assess the body composition of children with inflammatory bowel disease (IBD) and to study the accuracy of clinically available tools in predicting excess body fatness. We aimed at also exploring the influence of adiposity on pharmacokinetics during early Infliximab exposure. Methods: Prospective cohort study in 5- to 17-year-old children with IBD initiating Infliximab therapy. Patient demographic, phenotypic, and laboratory data at the time of Infliximab initiation were recorded. Body composition was assessed using air displacement plethysmography (ADP). fat mass index (FMI = fat mass [kg]/(height [m]) 2 ) was calculated to determine excess adiposity (defined as FMI ≥75th centile). Anthropometrics (weight, height, mid upper arm circumference [MUAC] and triceps skin fold thickness [TSF]) were obtained and MUAC and TSF measurements were used to calculate arm fat area (AFA) and arm muscle area z -scores. Statistical analysis was applied as appropriate. Results: Fifty-three (68% male; 55% Crohn disease [CD], 45% ulcerative colitis [UC], median [IQR] age 15 [13–16] years) children with IBD were included. Twenty-four percentage of children with IBD (21% CD, 29% UC) had excess adiposity. Four children (31%) with FMI ≥75th centile were not identified by body mass index (BMI) alone (kappa of 0.60), and 2 children (15%) were not identified by AFA z -score alone. The intra- and interobserver reliability of MUAC and TSFT measurements was excellent. There was no difference in Infliximab trough levels at the end of induction between those with FMI less than or ≥75th centile. Conclusions: Excess adiposity affects approximately 1 in 4 young patients with IBD and can be missed by routine obesity screening. Our exploratory study did not raise concerns of underexposure to infliximab in those children with excess adiposity during early drug exposure.